Characteristics and physiological basis of falls in ventricular outputs after immediate cord clamping at delivery in preterm fetal lambs. (3rd July 2021) - Smolich, Joseph J.; Kenna, Kelly R.; Phillips, Sarah E.; Mynard, Jonathan P.; Cheung, Michael M. M.; Lambert, Gavin W.
Abstract : Key points: Controversy exists about the physiological mechanism(s) underlying decreases in cardiac output after immediate clamping of the umbilical cord at birth. To define these mechanisms, the four major determinants of ventricular output (afterload, preload, heart rate and contractility) were measured concurrently in fetal lambs at 15 s intervals over a 2 min period after cord clamping and before ventilation following delivery. After cord clamping, right (but not left) ventricular output fell by 20% in the initial 30 s, due to increased afterload associated with higher arterial blood pressures, but both outputs then halved over 45 s, due to a falling heart rate and deteriorating ventricular contractility accompanying rapid declines in arterial oxygenation to asphyxial levels. Ventricular outputs subsequently plateaued from 75 to 120 s, associated with rebound rises in ventricular contractility accompanying asphyxia‐induced surges in circulating catecholamines. These findings provide a physiological basis for the clinical recommendation that effective ventilation should occur within 60 s after immediate cord clamping. Abstract: Controversy exists about the physiological mechanism(s) underlying large decreases in cardiac output after immediate clamping of the umbilical cord at birth. To define these mechanisms, anaesthetized preterm fetal lambs (127(1)d, n = 12) were instrumented with flow probes and catheters in major central arteries, and a left ventricular (LV) micromanometer‐conductance catheter. Following immediate cord clamping at delivery, haemodynamics, LV and right ventricular (RV) outputs, and LV contractility were measured at 15 s intervals during a 2 min non‐ventilatory period, with aortic blood gases and circulating catecholamine (noradrenaline and adrenaline) concentrations measured at 30 s intervals. After cord clamping, (1) RV (but not LV) output fell by 20% in the initial 30 s, due to a reduced stroke volume associated with increased arterial blood pressures, (2) both outputs then halved over the next 45 s, associated with falls in heart rate, arterial blood pressures and ventricular contractility accompanying a rapid decline in arterial oxygenation to asphyxial levels, (3) reduced outputs subsequently plateaued from 75 to 120 s, associated with rebound rises in blood pressures and ventricular contractility accompanying exponential surges in circulating catecholamines. These findings are consistent with a time‐dependent decline of ventricular outputs after immediate cord clamping, which comprised (1) an initial, minor fall in RV output related to altered loading conditions, (2) ensuing large decreases in both LV and RV outputs related to the combination of bradycardia and ventricular dysfunction during emergence of an asphyxial state, and (3) subsequent stabilization of reduced LV and RV outputs during ongoing asphyxia, supported by cardiovascular stimulatory effects of marked sympathoadrenal activation. Key points: Controversy exists about the physiological mechanism(s) underlying decreases in cardiac output after immediate clamping of the umbilical cord at birth. To define these mechanisms, the four major determinants of ventricular output (afterload, preload, heart rate and contractility) were measured concurrently in fetal lambs at 15 s intervals over a 2 min period after cord clamping and before ventilation following delivery. After cord clamping, right (but not left) ventricular output fell by 20% in the initial 30 s, due to increased afterload associated with higher arterial blood pressures, but both outputs then halved over 45 s, due to a falling heart rate and deteriorating ventricular contractility accompanying rapid declines in arterial oxygenation to asphyxial levels. Ventricular outputs subsequently plateaued from 75 to 120 s, associated with rebound rises in ventricular contractility accompanying asphyxia‐induced surges in circulating catecholamines. These findings provide a physiological basis for the clinical recommendation that effective ventilation should occur within 60 s after immediate cord clamping.